Relationship between workplace environments and the level of employees productivity in University College Bestari / Farah Nor Liyana Mazelan - Mazelan, Farah Nor Liyana (Faculty Of Business Management, 2017)
The research aims to study the Relationship between Workplace Environments and the Level of Employees Productivity in University College Bestari (UCB). The limitation of study was focused on the employees in UCB. The scope of this research is to focus on the Factor Physical Components of Environment and Level of Employees Productivity. The studied used descriptive corrective method. From the Krejcie and Morgan table (1970), the scope are focused on 190 number of population. The sample sizes taken are 127 people are referred size for a given population. The questionnaire were distributed to 127 respondents in UeB. The physical component of environment are divided in three section. The components in the workplace environment play an important role towards the employees productivity. This will give an immense impact to the employees either towards the negative or positive outcomes that will employees provide to the organization. On this study, it was focus three physical component of environment and the level of employees productivity. In the three physical component of environment it was consist of space planning, environment and color.